Determinantes das parasitoses intestinais em população infantil de assentamentos rurais do Município de Alegre, ES : um modelo de análise hierarquizado - Rocha, Renata Abdalla Pires da (2008)
The purpose of this study is to contribute to the understanding of the determinant factors of intestinal nematode among children that share the same socio economic condition in a rural area in the south of Espírito Santo State. This is a prevalence study in rural land settlement areas from the municipality of Alegre. The sample size was 133 children. It was collected blood and feces and performed a questionnaire from June to August, 2006. Then, it was conducted a hierarchial model and the data were analyzed by Statistical Package for the Social Sciences (SPSS) version 14.0. The results are seen in tree sections: first, the prevalence of intestinal nematodes and predictors variables, second, bivariate analysis and logistic regression model and third, the especial distribution of the cases. It was verified a prevalence of 21,80% of infected children. In the logistic regression by blocs we found a statistic significance between intestinal nematodes and father education, number of people at home, water supplies, habits of cleaning hands after using a bathroom, number of meals a day, seen a doctor in 2005, use of anti-nematode drugs and habits of cleaning hands before meals. In the final logistic regression, both models had the same variable statistic significance which was: number of people at home and water supplies. The data to present study confirms the need of public politics in order to improve the quality of life for this rural population and continuity of the studies on these areas is necessary to reach this marks.